2022
DOI: 10.51601/ijhp.v2i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug Storage Using FIFO/FEFO Methods In Royal Prima Medan Hospital Pharmacy Installation

Abstract: The inappropriate drug storage system can cause the drug to break down quickly, drug expiration, stockout, and drug stagnation. This study aims to evaluate the storage of drugs using the FIFO and FEFO methods in the Royal Prima Medan Hospital Pharmacy Installation Warehouse. This type of research is descriptive qualitative. The research samples were employees of Royal Prima Medan Hospital Pharmacy Installation Warehouse who had worked for ± 1 year. For the validity and reliability of the data, source triangula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Salah satu faktor yang menyebabkan kadaluwarsa obat adalah kurangnya pengendalian stok, seperti tidak menerapkan metode First in First Out (FIFO), First Expired First Out (FEFO), dan overstocking [7]. Selain itu menurut [8] penyimpanan obat menggunakan metode FIFO (First in First Out) dan FEFO (First Expired First Out) adalah metode penyimpanan obat yang telah banyak digunakan di berbagai instalasi farmasi rumah sakit Metode FIFO menilai inventaris dengan asumsi bahwa barang yang pertama dibeli atau diproduksi adalah yang pertama dijual atau digunakan, sehingga barang lebih awal masuk akan diprioritaskan untuk penggunaan atau penjualan [9]. Metode FIFO atau First In First Out dipilih karena barang pertama yang masuk ke dalam gudang atau toko akan diprioritaskan untuk dijual atau digunakan terlebih dahulu, sehingga barang terakhir yang masuk akan menjadi sisa persediaan [10].…”
Section: Pendahuluanunclassified
“…Salah satu faktor yang menyebabkan kadaluwarsa obat adalah kurangnya pengendalian stok, seperti tidak menerapkan metode First in First Out (FIFO), First Expired First Out (FEFO), dan overstocking [7]. Selain itu menurut [8] penyimpanan obat menggunakan metode FIFO (First in First Out) dan FEFO (First Expired First Out) adalah metode penyimpanan obat yang telah banyak digunakan di berbagai instalasi farmasi rumah sakit Metode FIFO menilai inventaris dengan asumsi bahwa barang yang pertama dibeli atau diproduksi adalah yang pertama dijual atau digunakan, sehingga barang lebih awal masuk akan diprioritaskan untuk penggunaan atau penjualan [9]. Metode FIFO atau First In First Out dipilih karena barang pertama yang masuk ke dalam gudang atau toko akan diprioritaskan untuk dijual atau digunakan terlebih dahulu, sehingga barang terakhir yang masuk akan menjadi sisa persediaan [10].…”
Section: Pendahuluanunclassified
“…do Nascimento Nunes et al (2014 demonstrated the heterogeneity of temperature of a pallet of berries and demonstrated the FIFO model leads to the waste of high value temperature sensitive products. The FEFO model has been suggested to be a superior to FIFO in food (Curto and Gaspar, 2021) as well as non-food products, such as pharmaceuticals (Sukasih et al, 2020;Rezeki et al, 2022). One of the primary challenges of FEFO is it requires information sharing between different members of the cold chain (Hertog et al, 2014).…”
Section: Introductionmentioning
confidence: 99%